Effect of Medicaments Used in Endodontic Regeneration on the Dislocation Resistance of MTA to Dentin - Noor AlSahwan; Shibu T. Mathew (Journal of Pharmacy and Bioallied Sciences)
Aim: The purpose of this study was to assess the push-out bond strength of mineral trioxide aggregate (MTA) to dentin after the use of intracanal medicaments, including calcium hydroxide [Ca(OH)2], calcium hydroxide with chlorhexidine [CHX], double antibiotic paste [DAP], and modified triple antibiotic paste [mTAP], for 3 and 6 weeks and identify the failure modes related to each medicament. Materials and Methods: Eighty extracted mandibular premolars were decoronated and instrumented to size 30 (Protaper Universal F3). Peeso reamers #1–#6, followed by 2.5% NaOCl, 17% EDTA, and distilled water for irrigation, were applied in sequence. The specimens were divided into four groups with n = 20/group: Group 1, Ca(OH)2; Group 2, Ca(OH)2 + CHX; Group 3, DAP; and Group 4, mTAP. The medicaments were deposited using a Lentulo spiral, and the samples were kept in saline at both 3 and 6 weeks. Results: MTA dislocation resistance significantly decreased with time, i.e., between 3 weeks and 6 weeks (P < 0.05). There was no significant difference at 3 weeks between Ca(OH)2 and Ca(OH)2 + CHX (P = 0.791) or at 6 weeks between Ca(OH)2 and mTAP (P = 1.000). Calcium hydroxide provided the highest bonding strength, while DAP had the lowest at both time points. Conclusion: The highest bond strength was shown by calcium hydroxide at both 3 and 6 weeks, while the lowest bond strength was obtained with DAP.